Penyuluhan dengan Multimedia untuk Meningkatkan Pengetahuan tentang Perilaku Hidup Sehat dan Bersih Siswa SMA - Ifa Roifah; Agus Novianto (Akademi Keperawatan Dharma Husada Kediri, 2014)
Children are future generations which are the most important asset in order to achieve Nation’s success to realize it is needed to apply Clean and Healthy Life Behaviors (PHBS) by no smoking, right personal hygiene, regular physical exercise, and no drugs by using multimedia method extension towards students’ knowledge of Clean and Healthy Life Behaviors (PHBS) on educational aspect in SMA Negeri 1 Gondang Mojokerto. The research design is used Pre-Experiment, which is applied One-Group Pre-Post Test Design. The populations of students which join School Health Program are 101 students, and the samples are 81 students taken by probability sampling (Simple Random Sampling). The independent variable is extension through multimedia method and the dependent variable is students’ knowledge about Clean and Healthy Life Behaviors (PHBS) on educational aspect. The data is taken by the using of puzzle game crosswords form which is use after and before extension. After all of data collected and data processing statistical test followed by Wilcoxon sign test SPSS17, the result showed Asymp.Sig value (2-tailed) of 0.000 and α of 0.05. Because Asymp.Sig value (2-tailed) <α 0.05 then H0is rejected and H1 is accepted, it means that there is an influence using multimedia method extension towards students’ knowledge of Clean and Healthy Life Behaviors (PHBS) on educational aspect in SMA Negeri 1 Gondang Mojokero. Key words: patients with violent behavior, nurse experience, qualitative